Kenna And Ledger’s Forgiveness As Realization Of Reconciliation In Colleen Hoover’s Reminders Of Him Novel - Johanes Claudio Perdana Napitupulu; Rommel Utungga Pasopati (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study explains about how the realization of reconciliation is seen by Kenna and Ledger’s forgiveness in a novel entitled Reminder’s of Him by Colleen Hoover in 2022. The writers on this article use qualitative method which can help the reader to explore more about the context of the object. This forgiveness shows how Kenna and Ledger can forgive each other and move forward into better future. The analysis look at how Kenna tries to reach forgiveness in order to escape from her past memories while Ledger wants Kenna forgive him for what he has done to her. In conclusion, the writers confirm that Kenna and Ledger get their better relationship while forgive each other and move forward into recconciliation.